Ustekinumab for the treatment of refractory pediatric Crohn’s disease: a single-center experience - Cohen, Alexandra (Intest Res, 2021)
BACKGROUND/AIMS: Despite the well-established efficacy of tumor necrosis factor (TNF) antagonists as treatment options for Crohn’s disease, many pediatric patients need a change in therapy due to adverse events and loss of response, highlighting the necessity for medications with a different mechanism of action. Ustekinumab has been shown to be effective in inducing clinical remission in some adults with disease refractory to anti-TNF agents, however, minimal data exists in the pediatric population. METHODS: We conducted a retrospective chart review of 11 pediatric patients receiving ustekinumab, specifically extracting baseline data, information on prior treatment and response, indications for starting ustekinumab, clinical information, and laboratory parameters pre- and post-therapy. Clinical response was defined as a decrease in abbreviated Pediatric Crohn’s Disease Activity Index score. RESULTS: Patients ranged from 12 to 17 years of age upon initiation of treatment with ustekinumab. Five of 11 patients demonstrated a clinical response. Among these patients, 2 remained in clinical remission, while the remaining 3 experienced a secondary loss of response. The other 6 patients were primary nonresponders who either remained unwell or demonstrated slight clinical worsening. All patients who clinically responded to ustekinumab and had an initially elevated CRP experienced complete normalization of their values. Mucosal healing was seen on endoscopy in 1 responder, with 2 other patients showing endoscopic improvement. CONCLUSIONS: These results demonstrate for the first time that ustekinumab has the potential to induce not only clinical and biochemical remission, but also endoscopic improvement, in the pediatric population. Future research is needed to determine factors that influence response to therapy.